2014
DOI: 10.1080/09168451.2014.946390
|View full text |Cite
|
Sign up to set email alerts
|

New series of avenanthramides in oat seed

Abstract: Avenanthramides are characteristic constituents of oat seeds. We analyzed the methanol extract of oat seeds by HPLC and detected three compounds 1, 2, and 3 eluted at retention times similar to avenanthramides. The three compounds were purified by column chromatography and HPLC. Spectroscopic analyses of 1, 2, and 3 suggested that they are amides of 4,5-dihydroxyanthranilic acid with caffeic, p-coumaric, and ferulic acids, respectively. Their identities were confirmed by comparing spectra and chromatographic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…The quantities of A1 varied from 40-132 μg/g among the 10 cultivars of oats tested. Recently a new series of AVs containing a 4,5-dihydroxyanthranilate moiety were purified using column chromatography and HPLC from oat seeds [61]. The structures of these AVs were elucidated by a LC-MS/MS analysis with multiple reaction monitoring.…”
Section: Avenanthramidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantities of A1 varied from 40-132 μg/g among the 10 cultivars of oats tested. Recently a new series of AVs containing a 4,5-dihydroxyanthranilate moiety were purified using column chromatography and HPLC from oat seeds [61]. The structures of these AVs were elucidated by a LC-MS/MS analysis with multiple reaction monitoring.…”
Section: Avenanthramidesmentioning
confidence: 99%
“…Table 2 outlines a brief overview of the extraction techniques, associated health benefits and commercial availability of the various bioactive components present in oat and barley. [61]. Bound phenolics-20 h prolonged alkaline hydrolysis [51];…”
Section: Proteins and Bioactive Peptidesmentioning
confidence: 99%
“…Fagerlund et al (2009) found that, compared with α-tocopherol, AVAs protected linoleic acid from oxidation initially to a smaller extent initially. Also, to prevent the oxidative reaction of unsaturated fatty acids, AVAs can easily be used in the food industry (Ishihara et al 2014) due to the radical scavenging effect (Singh et al 2013). Similarly, Liu et al (2011) studied the antioxidant ability of capsules containing oats AVAs on human body and found that oats extract containing AVAs possessed a high antioxidant activity on humans (Liu et al 2011).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…It is interesting that AVAs are very similar in their chemical structure to tranilast (N-3,4-dimethoxycinnamoylanthranilic acid), which is an antiallergic drug used to treat asthma and autoimmune diseases (Azuma et al 1976;Ishihara et al 2014). AVAs, having a similar structure to that of tranilast, can be used in the treatment of allergic reactions (Sur et al 2008).…”
Section: Effects Of Avenanthramides On Healthmentioning
confidence: 99%
See 1 more Smart Citation